Targeting STAT3 signaling in kidney disease - Pace, Jesse (Am J Physiol Renal Physiol, 2019)
The Janus kinase/signal transducer and activator of transcription (JAK/STAT) signaling pathway is a multifaceted transduction system that regulates cellular responses to incoming signaling ligands. STAT3 is a central member of the JAK/STAT signaling cascade and has long been recognized for its increased transcriptional activity in cancers and autoimmune disorders but has only recently been in the spotlight for its role in the progression of kidney disease. Although genetic knockout and manipulation studies have demonstrated the salutary benefits of inhibiting STAT3 activity in several kidney disease models, pharmacological inhibition has yet to make it to the clinical forefront. In recent years, significant effort has been aimed at suppressing STAT3 activation for treatment of cancers, which has led to the development of a wide variety of STAT3 inhibitors, but only a handful have been tested in kidney disease models. Here, we review the detrimental role of dysregulated STAT3 activation in a variety of kidney diseases and the current progress in the treatment of kidney diseases with pharmacological inhibition of STAT3 activity.